American classics [compact disc, unabridged] - Shen, Freda Foh; Strathairn, David; Channing, Stockard; Auberjonois, René, 1940-2019-; Baranski, Christine; Stiller, Jerry; De Lavallade, Carmen, 1931-; McCourt, Malachy, 1931-; Tan, Amy; Barthelme, Donald; Poe, Edgar Allan, 1809-1849; Oates, Joyce Carol, 1938-; et al. (Selected shorts (Radio program), 2010)
A collection of eight short stories by well-known American authors.